Endoscopic full‐thickness resection of an esophageal leiomyoma located in close proximity to the azygos vein. Issue 1 (25th August 2021) - Shiwaku, Hironari; Okada, Hiroki; Shiwaku, Akio; Tanaka, Keita; Shimaoka, Hideki; Maki, Kenji; Yoshimura, Fumihiro; Hasegawa, Suguru
Abstract: Third‐space endoscopic techniques, such as peroral endoscopic tumor resection (POET) and submucosal tunneling endoscopic resection (STER), enable access to deep organs and tissues that have been previously inaccessible with an endoscope. We present a 29‐year‐old man with a submucosal tumor (40 × 25 mm) located at 5 o'clock in the upper thoracic esophagus. Histological diagnosis by endoscopic ultrasound–fine needle aspiration was leiomyoma. Computed tomography showed the azygos vein posterior to the tumor. However, because endoscopic ultrasound revealed space between them, POET was performed. Because the tumor originated from the deep layer of the muscularis propria, full‐thickness resection was performed to achieve R0 resection. The azygos vein arch was seen through the mediastinal space after tumor enucleation. The final histopathological diagnosis was leiomyoma. POET is a potentially revolutionary endoscopic technique that enables full‐thickness resection of nonepithelial lesions. Preoperative computed tomography or endoscopic ultrasound to determine peritumoral anatomy is important to ensure safety. During the procedure, it is important to operate under direct vision, accurately identify the tumor boundary, and dissect along the boundary to avoid damaging the tumor and surrounding structures.